Effects of a chronic myositis on structural and functional features of spinal astrocytes in the rat - Tenschert, Sibylle; Hoheisel, Ulrich; Mense, Siegfried (Neuroscience letters, 2004)
The study aimed at the question if astrocytes react with morphological or functional changes when a skeletal muscle is pathologically altered. In rats, a myositis was induced in the gastrocnemius-soleus muscle. After 12 days, the immunoreactivity (IR) for glial fibrillary acidic protein (GFAP), morphometric parameters, and fibroblast growth factor-2 (FGF-2) expression of astrocytes were quantitatively evaluated in the dorsal horn of the spinal segment L4. Following inflammation, the area density of GFAP-IR as well as the proportion of astrocytes expressing FGF-2 increased significantly while the degree of astrocyte arborisation decreased as shown by a shape factor. The density of cell nuclei was unchanged suggesting that no myositis-induced cell divisions occurred. The data indicate that spinal astrocytes may influence pain processes particularly by increased FGF-2 synthesis.